FAKTOR YANG MEMPENGARUHI KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN RISIKO PERUSAHAAN (Studi empiris pada perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia periode 2015-2018) - Silitonga, Evalina (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
AbstractThis study aims to examine about factors which are influence corporate risk disclosure in LQ45 enterprise. Independent variables in this study is size, profitability, liquidity, solvability and type of industry. Dependent variable is corporate risk disclosure. The population used here was of LQ45 listed on the Indonesia Exchange Stock period of years 2015-2018. The sample was taken using the method of purposive sampling, and those meeting the selection criteria were also taken. The sample used was of 102 samples from 34 enterprise LQ45 period of 4 years (2015-2018). Risk disclosure in this research use content analysis based on identification of sentences act of risk disclosure in annual report. Research method that used for examining hypothesis is multiple regression analysis. The result of this research showed that size, profitabilit, liquidity, solvability and type of industry are positive related with corporate risk disclosure. Keywords: risk disclosure, firm characteristics, annual report.